Trans-Pacific Partnership (TPP) Agreement: Increased pressure on European trade policy - Hanns Günther Hilpert (Stiftung Wissenschaft und Politik (SWP), 2015)
After five years of intense negotiations, trade ministers of twelve Pacific Rim countries, including the United States, Canada, and Japan, have reached agreement on a comprehensive Trans-Pacific Partnership (TPP). Whether and when this agreement will come into effect depends above all on the ratification process in the US Congress. If ratified, the TPP will create the largest free trade zone worldwide. It will not only eliminate virtually all tariffs on trade and open up domestic markets extensively in the areas of agriculture and services, but also set binding minimum standards for trade and investment. The biggest "losers" under the TPP are the countries that are not part of the negotiations - especially two of the world's economic heavyweights: the EU and China. They are finding themselves increasingly on the defensive in trade policy. (SWP Comments)
Keywords: 320